Qualitative Analysis of Tencel A100 Fiber and Selected Regenerated Cellulose Fibers. Issue 2 (March 2017) - Gao, Youjun; Liu, Jinrui; Zhao, Sumin; Zhang, Xiangli
This research studies the solubility properties of certain regenerated cellulose fibers in commonly-used acidic reagents, including formic acid/zinc chloride. A dissolution method for qualitative identification of Tencel A100 (lyocell) fiber in the presence of various other regenerated cellulose fibers was established. This qualitative method was simple, rapid, and had high sensitivity.